2012
DOI: 10.4081/jlimnol.2012.e15
|View full text |Cite
|
Sign up to set email alerts
|

Benthic communities on hard substrates covered by Limnoperna fortunei Dunker (Bivalvia, Mytilidae) at an estuarine beach (Río de la Plata, Argentina)

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
0
8
0
5
Order By: Relevance
“…Blocking of pipes, turbines and obstructions in water treatment plants are the consequences that are the most costly to repair. Impacts *e-mail: nakamuraaf@gmail.com on the natural populations can be irreversible causing rapid transformation in the communities of benthic macroinvertebrates 14,15 . The objective of this study was to characterize the microstructures and to determine the calcium carbonate phases present in the shell of L. fortunei to help to understand the processes involved in the formation of the shell (biomineralization), aiming to promote the creation of new controlling methods this invasive specie.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking of pipes, turbines and obstructions in water treatment plants are the consequences that are the most costly to repair. Impacts *e-mail: nakamuraaf@gmail.com on the natural populations can be irreversible causing rapid transformation in the communities of benthic macroinvertebrates 14,15 . The objective of this study was to characterize the microstructures and to determine the calcium carbonate phases present in the shell of L. fortunei to help to understand the processes involved in the formation of the shell (biomineralization), aiming to promote the creation of new controlling methods this invasive specie.…”
Section: Introductionmentioning
confidence: 99%
“…This increased siltation seems to modify macroinvertebrate assemblages, favouring the abundance of many groups like annelids and nematodes (Duchini, Boltovskoy, & Sylvester, ). However, the effect of L. fortunei over macrobenthic communities remains largely unknown, although many authors have suggested potential risks for native mollusc biodiversity (Martin & Darrigran, ; Scarabino & Verde, ; Spaccesi & Rodrigues Capitulo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of C. fluminea, both the density and distribution range increased, reaching densities of between 300 and 1000 individuals m À2 in the Lower Delta of the Paran a River (Boltovskoy and Cataldo, 1999). Similarly, the golden mussel L. fortunei has rapidly expanded its distribution range (Darrigran, 2002), with densities of nearly 380 000 individuals m À ² recorded in the middle zone of the R ıo de la Plata estuary (Spaccesi and Rodrigues Cap ıtulo, 2012); its presence thus adds new species to the food web for fishes.…”
Section: Introductionmentioning
confidence: 99%